Metode Internalisasi Nilai-Nilai Multikultural di Asrama SMA Negeri 1 Matauli Pandan Tapanuli Tengah Provinsi Sumatera Utara - Ano Suherlan (Studi Multidisipliner: Jurnal Kajian Keislaman, 2020)
The method of internalizing multicultural values in the SMA Negeri 1 Matauli Pandan Tapanuli Tengah dormitory was carried out in various ways, including modeling, habituation, association and rule enforcement and teachers providing space for internalizing multicultural values, integrated with students in SMA dormitories. Negeri 1 Matauli Pandan Tapanuli Tengah. The internalization of multicultural values has gone well, students can live peacefully, have principles, apply a class organization system, democratic values, respect equality or gender, live in justice, tolerate between religions, respect human rights, and strengthen unity.